The effects of fasting during Ramadan on the concentration of serotonin, dopamine, brainderived neurotrophic factor and nerve growth factor - Abdolhossein Bastani; Sadegh Rajabi; Fatemeh Kianimarkani (MDPI AG, 2017)
Neurotransmitters and neurotrophic factors are signaling molecules that play a crucial role in cell proliferation, differentiation, survival and functions of neurons. It is believed that caloric restriction could help the health of the nervous system by affecting the synthesis of neurotrophins and neurotransmitter and oxygen radical metabolism. The objective was to investigate the plasma levels of serotonin, dopamine, brain-derived neurotrophic factor (BDNF), and nerve growth factor (NGF) in 29 healthy fasted subjects (22 women and 7 men) during the month of fasting in Ramadan. The levels of these factors were measured (using ELISA method) three times, 2 days before the fasting month as a control, on the 14th and 29th day of Ramadan as test groups. In addition, these factors were investigated in the group of women only. According to our investigation, the plasma levels of serotonin, BDNF and NGF were significantly increased during fasting month of Ramadan. In detail, the levels of these factors were increased in 14th and 29th day test groups compared to controls (P<0.05). Moreover, these levels were significantly increased on the 29th day compared to the 14th day test groups, but there were no differences between dopamine levels in all groups. Furthermore, the results obtained in women's groups were the same as those obtained in previous groups. Our findings suggest that plasma levels of serotonin, BDNF and NGF were significantly increased during fasting month of Ramadan.